HUBUNGAN ANTARA NILAI UNCONFINNED COMPRESSION TEST DENGAN LIQUID LIMIT (LL) DAN LIQUDITY INDEX (LI) - Athiyah Saulawani; Ely Mulyati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Clay soil is a type of soil with high plasticity whose properties are strongly influenced by water content. The consistency of clay can be represented by the Liquid Limit (LL) and Liquidity Index (LI), while its strength is commonly evaluated using the Unconfined Compression Test (UCT), which is widely applied in geotechnical analysis. This study aims to analyze the relationship between UCT values and soil consistency index parameters (LL and LI). Soil samples were taken from three different locations and compacted according to the Standard Proctor test as a reference for preparing unconfined compression test specimens. The test results show that the LL values at the three locations were 56.37%, 60.91%, and 42.43%, while LI values ranged from -0.47 to -0.04, indicating soil conditions from dense to slightly plastic. The unconfined compressive strength (qu) at the optimum water content was 14.91 kg/cm² at Location 1, 12.50 kg/cm² at Location 2, and 13.20 kg/cm² at Location 3. Correlation analysis indicates a weak relationship between qu and LL, while qu and LI exhibit a relatively high R² value. However, due to the very limited amount of data, the relationship between these parameters cannot yet be conclusively determined.Keywords: Clay soil, Unconfined Compression Test (UCT), Liquid Limit (LL), Liquidity Index (LI), Compaction